Isobaric vapor-liquid equilibrium data for the binary systems of dimethyl carbonate with xylene isomers at 93.13 kPa - Yadav, S.S. (Journal of Chemical and Engineering Data, 2017)
Isobaric binary vapor-liquid equilibrium (VLE) data for dimethyl carbonate with xylene isomers (p-xylene, m-xylene, o-xylene, and ethylbenzene) were measured at the local atmospheric pressure of 93.13 kPa by using a dynamic recirculation still. The experimental VLE data were tested and found to be thermodynamically consistent by Herington and Van Ness consistency test. The experimental VLE data were correlated using the Wilson, NRTL, and UNIQUAC activity coefficient models and binary interactions parameters were estimated using a suitable objective function. The absolute mean deviation between the experimental and the model predicted values of vapor phase composition and total pressure was well within acceptable limits. No azeotrope was observed in any of the binary pairs and appeared to be easy for separation using conventional distillation method.
Keywords: Atmospheric Pressure; binary mixture; Distillation; Xylene